Values of Our Times Contemporary Axiological Research in China - Li, Deshun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Philosophers have gradually accepted axiology as one branch of philosophy. As a basic category belonging to axiology and philosophy, "value" is the general abstraction of concrete value formation in various fields including utility, ethics and appreciation of the beauty. The problem of value is essentially a problem of historical activities of practice in human society. The axiology based on the scientific practice view insists on the principle of unification between theory and practice, truth and value. In research of axiology, the relation between subjectivity and objectivity of values is a problem that must be solved in the first place. The modern conversation of value philosophy is the academic and practical demands of the value philosophy research in China. Value evaluation is an important part of the axiology. In order to deepen the research of value philosophy and to promote the development of current value philosophy, we must have scientific mode of thinking suitable for the nature of value. It is the base of value relation, the origin of value needs, the process of value creation and actualization and the fundamental way to proving ones value as a human being.
Introduction: A New Approach to Contemporary Studies on Axiology -- Part one: The gist of Values and Contemporary Philosophy -- Value and Time -- (3z(BTo Be(3y (Bof Value: A Direction of the Research into the Essence of Value -- The Course of Human Subjectivity -- Value Is Human Being Itself and Human Self-realization -- A Philosophy that Addresses Chinese Issues -- A Milestone in the Development of the Philosophy of Value: Deng Xiaoping's Important Contribution to the Philosophy of Value -- Change from abstract value philosophy to realistic value philosophy -- Wanted: dialogue at the level of value beliefs among Chinese, Western and Marxist philosophies -- Part two: Towards the Depth of Human Life -- Interactivity between Virtue and Wisdom -- On the Transformation of Value Orientation of Commodity Symbols: Some Philosophical Considerations on Spiritual Transformation of Consumptive Activities -- The Social Self-criticism on the Threshold of Evaluation: Thinking on the Thought of Marx$1 (Bs Social Self-criticism -- On the Intimate Relation Between Social Facts and Three Types of Values -- The Practical Survival State of Public Society and the Occurrence of the Reasonable Value Experience -- On Marx$1 (Bs Politic Economic Method of Value -- Historical Understanding and Historical Appraisal -- A Brief Study of the Hierarchy Value Thought of the Pre-Qin Confucianism -- Part Three: Value Conceptions and Value Practice -- An Analysis of the Concept of Justice from the Perspective of Value Theory -- How is Environmental Ethics Possible$1!+; (B-- Ideal of Social Values for Hermeneutics of Human History -- Three Dimensions of the Formation of Values -- On the Value Orientation of Modern Market Economic System -- Three Doubts about the Comparison between Western and Chinese Views of Harmony from the Perspective of Axiology -- The core issue of values and the prepositional criticism of the answer -- The Value Basis of Evidence Rules -- The Connotation of Rule of Law: in the View of Axiology.s
Keywords: Philosophy (General).; Philosophy; Philosophy